Decrease in short‐latency afferent inhibition during corticomotor postexercise depression following repetitive finger movement. Issue 7 (9th June 2017) - Miyaguchi, Shota; Kojima, Sho; Sasaki, Ryoki; Kotan, Shinichi; Kirimoto, Hikari; Tamaki, Hiroyuki; Onishi, Hideaki
Abstract: Introduction: This study aimed to clarify cortical circuit mechanisms contributing to corticomotor excitability during postexercise depression (PED) following repetitive nonfatiguing movement. We investigated changes in short‐latency afferent inhibition (SAI) and short‐interval intracortical inhibition (SICI) by paired‐pulse transcranial magnetic stimulation (TMS) during PED. Methods: A total of 16 healthy subjects performed repetitive abduction movements of the right index finger at 2.0 Hz for 6 min at 10% maximum voluntary contraction. We measured SAI evoked by pairing ulnar nerve stimulation with TMS (interstimulus interval, 22 ms) before and during PED ( n  = 10, experiment 1). We also measured SICI evoked by paired TMS (interstimulus interval, 2 ms) at 80% resting motor threshold ( n  = 10, experiment 2), and at 80% active motor threshold ( n  = 8, experiment 3) before and during PED. Results: Single motor evoked potential amplitude significantly decreased 1–2 min after the movement task in all experiments, indicating reliable PED induction. In experiment 1, SAI significantly decreased (disinhibited) 1–2 min during PED, whereas in experiments 2 and 3, SICI showed no significant change during PED. Conclusion: This study suggests that cholinergic inhibitory circuit activity decreases during PED following repetitive nonfatiguing movement, whereas GABAA circuit activity remains stable. Abstract : We investigated cortical circuit mechanisms contributing to corticomotor excitability during postexercise depression (PED) following repetitive nonfatiguing movement by measuring changes in cholinergic‐dependent short‐latency afferent inhibition (SAI) and GABAA receptor‐dependent short‐interval intracortical inhibition (SICI) using transcranial magnetic stimulation (TMS). In the results, although SAI significantly decreased 1–2 min after the movement task, SICI showed no significant change. This study suggests that cholinergic inhibitory circuit activity decreases during PED following repetitive nonfatiguing movement, whereas GABAA circuit activity remains stable.